The crown of the Regina Scientiarum in South Africa - Erna Oliver; Willem H. Oliver (Verbum et Ecclesia)
The early notion of European Universities that developed on a Christian foundation where Theology occupied a special place got lost in the chaos of change brought about by the fourth revolutions world. In addition to these pressures, Theology in South Africa is further constrained by internal demands for transformation at various levels. This research focuses on determining if the education of Theology is still relevant within the current context, how Theological education can and should link to the current eras’ demands, and finally how and why Theology should keep informing and speaking to the three ‘publics’ (Tracy) and the six ‘inters’ (Richardson) to adapt to the new normal of chaotic change – however, at the same time to also stay true to her unique Christian calling. Despite the weight of the demands made from both outside and inside academic circles on Theology as a discipline, it is the responsibility of theological educators to keep the crown intact by letting the light of Christ shine both inside and outside academia.